Determination of ureA and hopQ gene expression of Helicobacter pylori strains under acid stress conditions (2023)
ABSTRACT: Acid pH induces transcriptional changes that affect the expression of Helicobacter pylori (H. pylori) ureA and hopQ genes, which may be adaptive mechanisms to acid stress conditions that are expressed differently depending on the virulence of the bacterium. However, the relationship between gene expression and virulence profile requires further studies, so we evaluated the effect of different pH values on the expression of ureA and hopQ genes of H. pylori strains with high and low virulence profiles. Methods: Two H. pylori isolates with high virulence and low virulence profiles that were exposed to pH 3.0, 4.0, 6.0 and 7.0 for one hour under microaerophilic conditions were used. Subsequently, RNA was extracted from the isolates and cDNA was obtained to identify the differential expression of the H. pylori ureA and hopQ genes by semiquantitative real-time PCR. The results obtained did not present a normal distribution due to the small number of samples used; therefore, nonparametric tests such as the Mann-Whitney U test were used. Results: This study revealed that UreA gene expression is higher in strains with a high virulence profile while hopQ gene expression increases in strains with a low virulence profile when subjected to acid stress. This result suggests that depending on the type of virulence, H. pylori uses different mechanisms to colonize and adapt to the gastric environment and its pH fluctuations. Conclusion: The results showed that in these two isolates with different virulence profiles there is an important effect of pH on the regulation of the expression of the ureA and hopQ genes. This possibly indicates that the change in pH will condition the adaptation mechanisms of each strain or isolate to the conditions of the gastric environment.